Análise da dieta e condição de saúde bucal em pacientes gestantes - Moimaz, Suzely Adas Saliba [UNESP]; Zina, Lívia Guimarães [UNESP]; Serra, Fernanda Assis Paiva [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2010)
Objectve: To perform a critical analysis of the diet record model adopted, to evaluate the cariogenicity of the maternal diet, and the incidence of dental caries in pregnant women treated at a prevent on clinic in an undergraduate dental course. Method: A cross-sectional study was performed with consultations to the database of the clinic and review of patients' charts and diet records. The sample was calculated and 205 patents were randomly selected. Bivariate statistical analysis was done at a significance level of 5% (α=0.05), using the statistical soft wares Epi Info versão 3.2, GraphPad Instat 3.6 and BioEstat. Results: The analysis of the diet records showed that 68.8% of the pregnant women presented a cariogenic diet, with high frequency of ingest on of fermentable carbon hydrates, mainly sucrose, with liquid consistency, and preferably consumed between the main meals. There was higher trend of the pregnant women mentioning a low frequency of carbon hydrate ingestion during the interview, while registering a diet rich of these components in their diet records (p<0.0001). The mean DMFT of the patients was 13.9 ± 5.4. There was no statistically significant association between diet and oral health variables (p>0.05). Conclusion: The diet record was proven an effective and valid method, if correctly employed. The prevalence of dental caries in the group of pregnant women was high and, although more than half of the sample presented a cariogenic diet, a significant association between diet and co-factors was not found.
Analysis of the diet and oral health condition in pregnant patients
Keywords: Cariogenic diet; Diet; Diet records; Oral health; Pregnant women